Genetic Susceptibility and Predictors of Paradoxical Reactions in Buruli Ulcer. - Yves Thierry Barogui; Sandor-Adrian Klis; Roch Christian Johnson; Richard O Phillips; Eveline van der Veer; Cleo van Diemen; Tjip S van der Werf; Ymkje Stienstra (PLoS Neglected Tropical Diseases)
Introduction Buruli ulcer (BU) is the third most frequent mycobacterial disease in immunocompetent persons after tuberculosis and leprosy. During the last decade, eight weeks of antimicrobial treatment has become the standard of care. This treatment may be accompanied by transient clinical deterioration, known as paradoxical reaction. We investigate the incidence and the risks factors associated with paradoxical reaction in BU. Methods The lesion size of participants was assessed by careful palpation and recorded by serial acetate sheet tracings. For every time point, surface area was compared with the previous assessment. All patients received antimicrobial treatment for 8 weeks. Serum concentration of 25-hydroxyvitamin D, the primary indicator of vitamin D status, was determined in duplex for blood samples at baseline by a radioimmunoassay. We genotyped four polymorphisms in the SLC11A1 gene, previously associated with susceptibility to BU. For testing the association of genetic variants with paradoxical responses, we used a binary logistic regression analysis with the occurrence of a paradoxical response as the dependent variable. Results Paradoxical reaction occurred in 22% of the patients; the reaction was significantly associated with trunk localization (p = .039 by Χ(2)), larger lesions (p = .021 by Χ(2)) and genetic factors. The polymorphisms 3'UTR TGTG ins/ins (OR 7.19, p < .001) had a higher risk for developing paradoxical reaction compared to ins/del or del/del polymorphisms. Conclusions Paradoxical reactions are common in BU. They are associated with trunk localization, larger lesions and polymorphisms in the SLC11A1 gene.